KTP Laser Treatment of Early Glottic Cancer: A Multi-Institutional Retrospective Study. (January 2021) - Parker, Noah P.; Weidenbecher, Mark S.; Friedman, Aaron D.; Walker, Brian A.; Lott, David G.
Objectives: The primary objectives were to report oncologic outcomes of transoral laser microsurgery with potassium-titanyl-phosphate (KTP) laser (TLM-KTP) ablation of early glottic cancer (EGC). The secondary objectives were to report vocal outcomes and to analyze factors that might influence outcomes. Methods: A multi-institutional, retrospective analysis of consecutive patients treated for T1 or T2 glottic squamous cell carcinoma undergoing TLM-KTP ablation with at least 2 years of follow-up was performed. Patients with prior radiation or surgery for laryngeal disease were excluded. Primary outcome measures included: surgical failures requiring radiation or laryngectomy, disease-specific survival (DSS), and overall survival (OS). Secondary outcome measures included: pre- and postoperative Voice Handicap Index-10 (VHI-10) scores. The effects of smoking status, stage, and anterior commissure involvement on outcomes were analyzed. Results: Overall 88 patients met inclusion criteria (83% male, 79.5% current or former smokers). Mean age was 68 (standard deviation (SD): 12). Mean follow-up was 39.5 months (SD: 15.3). Staging included 50 T1a, 21 T1b, and 20 T2 tumors, including three metachronous second primaries. Radiation and/or laryngectomy avoidance was achieved in 87/88 (98.9%) of patients, inclusive of 24 patients requiring KTP re-treatments. Two patients had biopsy-proven recurrence (2.3%), but only 21 of 24 re-treated patients received a formal biopsy. No patients died from laryngeal cancer. DSS and OS were 100% and 92.3%, respectively. The mean VHI-10 scores were 19.3 preoperatively, 3.8 at 6-months postop, and 3.8 at 2-years postop. Smokers had a longer interval to re-treatment ( P  = .03), patients with T2 lesions had a shorter interval to re-treatment (0.02), and patients with T2 lesions presented with worse initial VHI-10 scores (0.002). Conclusions: A multi-institutional, retrospective case series of TLM-KTP ablation of EGC demonstrated excellent oncologic outcomes when close surveillance and proactive re-treatments were utilized. Disease-specific survival, overall survival, and vocal function were excellent. Additional studies are necessary to further analyze the merits and risks of this treatment approach.